(untitled) (Global Journal of Medical Research, 2015)
Background: Hypertension (HTN), or high blood pressure (systolic blood pressure >140 mmHg and diastolic blood pressure >90 mmHg) is an overwhelming global challenge which ranks third as a cause of disability-adjusted life-year. Hypertension causes 7.1 million premature deaths each year worldwide and accounts for 13% of all deaths globally. There are effective medical therapies for hypertension management; but the problem of non-adherence to medical treatment remains a challenge for the medical professionals and social scientists. The objective of this study is to assess the magnitude of adherence and factors for non adherence related to anti-hypertensive treatments in hypertensive patients visiting Adama Referral Hospital.